2020
DOI: 10.3390/w12123300
|View full text |Cite
|
Sign up to set email alerts
|

Application of Irrigation Water Quality Indices and Multivariate Statistical Techniques for Surface Water Quality Assessments in the Northern Nile Delta, Egypt

Abstract: Under sustainable development conditions, the water quality of irrigation systems is a complex issue which involves the combined effects of several surface water management parameters. Therefore, this work aims to enhance the surface water quality assessment and geochemical controlling mechanisms and to assess the validation of surface water networks for irrigation using six Water Quality Indices (WQIs) supported by multivariate modelling techniques, such as Principal Component Regression (PCR), Support Vector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 75 publications
(92 reference statements)
2
52
0
Order By: Relevance
“…By contrast, the PLSR and PLR methods are easy and do not need several steps for calculating the PLI. The multivariate regression models such as PLSR and MLR have recently been used as alternative methods to predict the water quality indices based on data for several trace elements [37,39].…”
Section: Assessment Of Contamination Risk Using Geoaccumulation Indexmentioning
confidence: 99%
See 3 more Smart Citations
“…By contrast, the PLSR and PLR methods are easy and do not need several steps for calculating the PLI. The multivariate regression models such as PLSR and MLR have recently been used as alternative methods to predict the water quality indices based on data for several trace elements [37,39].…”
Section: Assessment Of Contamination Risk Using Geoaccumulation Indexmentioning
confidence: 99%
“…To the best of our knowledge, the issue of predicting PLI using PLSR and MLR models, based on trace element data, has not been addressed to date. The multivariate regression models were recently shown to perform well in predicting the water quality indices [37,39]. For example, Gad et al [37] found that PLSR based on data for several trace elements accurately estimated four pollution indices for water and the drinking water quality index (DWQI) for both the Cal.…”
Section: Assessment Of Contamination Risk Using Geoaccumulation Indexmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, users of irrigation water may experience a range of effects due to changes in WQ. The most common WQ-related problems in irrigated agriculture are those related to [32,37,38]:…”
Section: Selection Of Key Water Quality Parametersmentioning
confidence: 99%